Emerging medical applications based on non-ionizing electromagnetic fields from 0 Hz to 10 THz - Mattsson MO (Dove Medical Press, 2019)
Mats-Olof Mattsson,1,2 Myrtill Simkó1,2 1SciProof International AB, Östersund, Sweden; 2Strömstad Akademi, Institute for Advanced Studies, Strömstad, SwedenCorrespondence: Mats-Olof MattssonSciProof International AB, Vaktpoststigen 4, Östersund S-83132, SwedenTel +36 202 350 5825Email mats-olof.mattsson@sciproof-international.seAbstract: The potential for using non-ionizing electromagnetic fields (EMF; at frequencies from 0 Hz up to the THz range) for medical purposes has been of interest since many decades. A number of established and familiar methods are in use all over the world. This review, however, provides an overview of applications that already play some clinical role or are in earlier stages of development. The covered methods include modalities used for bone healing, cancer treatment, neurological conditions, and diathermy. In addition, certain other potential clinical areas are touched upon. Most of the reviewed technologies deal with therapy, whereas just a few diagnostic approaches are mentioned. None of the discussed methods are having such a strong impact in their field of use that they would be expected to replace conventional methods. Partly this is due to a knowledge base that lacks mechanistic explanations for EMF effects at low-intensity levels, which often are used in the applications. Thus, the possible optimal use of EMF approaches is restricted. Other reasons for the limited impact include a scarcity of well-performed randomized clinical trials that convincingly show the efficacy of the methods and that standardized user protocols are mostly lacking. Presently, it seems that some EMF-based methods can have a niche role in treatment and diagnostics of certain conditions, mostly as a complement to or in combination with other, more established, methods. Further development and a stronger impact of these technologies need a better understanding of the interaction mechanisms between EMF and biological systems at lower intensity levels. The importance of the different physical parameters of the EMF exposure needs also further investigations.Keywords: pulsed electromagnetic fields, low frequency electromagnetic fields, high frequency electromagnetic fields, millimeter waves, THz waves, bone healing, cancer treatment, neurological treatment, diathermy